Anti-Phospholipid Antibodies in COVID-19 Are Different From Those Detectable in the Anti-Phospholipid Syndrome - Borghi, Maria Orietta; Beltagy, Asmaa; Garrafa, Emirena; Curreli, Daniele; Cecchini, Germana; Bodio, Caterina; Grossi, Claudia; Blengino, Simonetta; Tincani, Angela; Franceschini, Franco; Andreoli, Laura; Lazzaroni, Maria Grazia; et al. (Frontiers in Immunology, 2020)
Background. Critically ill patients with coronavirus disease 2019 (COVID-19) have a profound hypercoagulable state and often develop coagulopathy which leads to organ failure and death. Because of a prolonged activated partial-thromboplastin time (aPTT), a relationship with anti-phospholipid antibodies (aPL) has been proposed, but results are controversial. Functional assays for aPL (i.e., lupus anticoagulant) can be influenced by concomitant anticoagulation and/or high levels of C reactive protein. The presence of anti-cardiolipin (aCL), anti-beta2-glycoprotein I (anti-2GPI) and anti-phosphatidylserine/prothrombin (aPS/PT) antibodies was not investigated systematically. Epitope specificity of anti-2GPI antibodies was not reported. Objective. To evaluate the prevalence and the clinical association of aPL in a large cohort of COVID-19 patients, and to characterize the epitope specificity of anti-2GPI antibodies. Methods. ELISA and chemiluminescence assays were used to test 122 sera of patients suffering from severe COVID-19. Of them, 16 displayed major thrombotic events. Results. Anti-2GPI IgG/IgA/IgM were the most frequent in 15.6/6.6/9.0% of patients, while aCL IgG/IgM were detected in 5.7/6.6% by ELISA. Comparable values were found by chemiluminescence. aPS/PT IgG/IgM were detectable in 2.5 and 9.8% by ELISA. No association between thrombosis and aPL was found. Reactivity against domain 1 and 4-5 of 2GPI was limited to 3/58 (5.2%) tested sera for each domain and did not correlate with aCL/anti-2GPI nor with thrombosis. Conclusions. aPL show a low prevalence in COVID-19 patients and are not associated with major thrombotic events. aPL in COVID-19 patients are mainly directed against 2GPI but display an epitope specificity different from antibodies in antiphospholipid syndrome.